MicroRNA: A new player in response to therapy for colorectal cancer. Issue 6 (27th November 2018) - Sarvizadeh, Mostafa; Malekshahi, Ziba V.; Razi, Ebrahim; Sharifi, Hossein; Moussavi, Nousin; Taghizadeh, Mohsen
Abstract: Colorectal cancer (CRC) is one of the important malignancies that result in cancer‐related deaths worldwide. Multiple lines of evidence have indicated that different responses to therapy in CRC cells led to the failure of the current therapies. Hence, identification of the underlying cellular and molecular pathways involved in the emergence of different responses from CRC cells could contribute to finding and designing new therapeutic platforms to overcome the present limitations. Among the various targets involved in CRC pathogenesis, microRNAs (miRNAs) have key roles in many signaling pathways that are associated with the initiation and progression of CRC. Increasing evidence has confirmed that miRNAs as epigenetic regulators could play critical roles in the response (resistance or sensitivity) to therapy. Cancer stem cells are well‐known players in resistance to therapy in CRC. They have been shown to play significant roles via inhibition and activation of many miRNA networks. Hence, miRNAs could be involved in the resistance and sensitivity of therapy in CRC cells via affecting different mechanisms, such as activation of cancer stem cells. Here, we summarized the role of various miRNAs in response to therapy of CRC cells. Moreover, we highlighted the roles of these molecules in the function of cancer stem cells, which are known as important players in the resistance to therapy in CRC.